The role of tax law in the national economy - Maulana, Ayang Fristia; Febriyanti, Afi Nurul; Hidayah, Jihan; Azzahra, Siti Alivia; Darly, Doddy (Institute Of computer Science (IOCS), 2024)
The purpose of our research is to discuss